Analisis Penafsiran al-Thabari Terhadap Ayat-Ayat Tabarruj - Amir, Ulfah Auliah ulfah; Mahmud, Basri (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
This study aims to uncover the meaning of Tabarruj according to al-Thabari in tafsir Jami' al-Bayan An Ta'wil Ay al-Qur'an. This study is a literature review that uses primary data from Qur'anic verses related to Tabarruj, as well as secondary data in the form of al-Tabari's interpretation of Tabarruj in his tafsir. The data is then reduced and compiled, and verified to arrive at a conclusion. The results showed that the word Tabarruj only appears once in the Qur'an, but there are related variants of the word, such as al-Buruj which appears 4 times, al-Mutabarrijaj in one verse, and Tabarrajna in one other verse. From these verses, it can be defined that Tabarruj is the act of a woman deliberately displaying her beauty and adornment to men who are not her muhrim. This is a forbidden behavior and has negative effects such as damaging self-honor, bringing disaster from God, and can trigger adultery.